Preparation of efficient organogelators based on pyrazine-2,5-dicarboxylic acid showing room temperature mesophase - Huang, Yaodong; Yuan, Yuqin; Tu, Wei; Zhang, Yan; Zhang, Meijie; Qu, Hongmei (Tetrahedron, 2015)
A new series of 3,6-dimethyl-pyrazine-2,5-dicarboxylic acid derivatives were synthesized and both their gelation abilities and thermotropic properties were studied. These compounds are efficient organogelators and easily form stable gels in many organic solvents. Moreover, they are room temperature liquid crystals, which all show hexagonal columnar mesophase. Results of 1H nuclear magnetic resonance (1H NMR), Fourier transform infrared spectroscopy (FTIR) and ultra-violet-visible spectroscopy (UV) showed the driving forces of gelation are intra-hydrogen bonding, π–π stacking and van der Waals interaction. On the other hand, the intra-hydrogen bonding may be essential to the formation of mesophase. A Teas plot was constructed to estimate the gel formation of four synthesized pyrazinecarboxamides in organic solvents. [Display omitted]